2008
DOI: 10.1038/sj.jid.5701011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hapten-Induced, Murine Model with Multiple Features of Atopic Dermatitis: Structural, Immunologic, and Biochemical Changes following Single Versus Multiple Oxazolone Challenges

Abstract: Atopic dermatitis (AD) is a chronic dermatosis bearing clinical, histological, and immunologic similarities to chronic allergic contact dermatitis (ACD). AD shows a Th2 cell-dominant inflammatory infiltrate, elevated serum IgE levels, a permeability barrier abnormality, and Staphylococcus aureus colonization. Repeated hapten challenges reportedly produce a Th2-like hypersensitivity reaction (Th2-like HR). Here, 9-10 challenges with oxazolone (Ox) to hairless mice also produced a chronic Th2-like HR. Permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
258
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(283 citation statements)
references
References 68 publications
(77 reference statements)
20
258
1
4
Order By: Relevance
“…Animals were divided into four groups (A, B, C, and D) containing four animals per group (Table V). Ten microliter of oxazolone (5% w/v in ethanol) was topically applied daily for a week to animals of group B, C, and D. After 1 week, the oxazolone-treated groups were further treated topically with 60 μL oxazolone (0.1% w/v in ethanol) once every alternate day for an additional 2-week period (19). After half an hour of oxazolone application, cetirizine cream base formulation and cetirizine EV gel each containing 1.0 mg drug was applied daily on the back of animals of groups C and D, respectively.…”
Section: Skin Sensitivity Studies and Histopathological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were divided into four groups (A, B, C, and D) containing four animals per group (Table V). Ten microliter of oxazolone (5% w/v in ethanol) was topically applied daily for a week to animals of group B, C, and D. After 1 week, the oxazolone-treated groups were further treated topically with 60 μL oxazolone (0.1% w/v in ethanol) once every alternate day for an additional 2-week period (19). After half an hour of oxazolone application, cetirizine cream base formulation and cetirizine EV gel each containing 1.0 mg drug was applied daily on the back of animals of groups C and D, respectively.…”
Section: Skin Sensitivity Studies and Histopathological Examinationmentioning
confidence: 99%
“…AD with signs of acute erythema and pruritus was produced by oxazolone challenge on the back skin of mice (19). While a single oxazolone challenge to hairless mice skin produces an acute AD, 9-10 oxazolone challenges over a 3-week period provoked a persistent chronic dermatosis with evidence of moderate to severe pruritus.…”
Section: In Vivo Pharmacodynamic Evaluationmentioning
confidence: 99%
“…Since the seminal work of the McLean Lab has underscored the importance of skin barrier abnormalities as an etiological factor in AD, we focused on the effects of coal tar on the epidermal biology of this disease (1, 3, 8). Our results reveal a key role of the AHR signaling pathway in breaching the vicious The immunopathogenesis of AD has been studied directly on patients or in animal models based on allergic immune responses (29)(30)(31). We have recently developed in vitro organotypic models for psoriasis and AD (18,19), and have shown that the application of genetic techniques in these models could be used to study epidermal aspects of diseases (32).…”
Section: Figurementioning
confidence: 99%
“…Because CD25pos cells produced higher levels of IL-2 than the CD25neg ones did (Fig. 1F), we set out to investigate the response of these two subsets in vivo in the context of chronic oxazolone-induced contact sensitivity (35). To this purpose, we compared WT cells to CD25KO cells, as well as sorted CD25pos and CD25neg cells.…”
Section: Differential In Vivo Responses Of Cd25pos and Cd25neg Mast Cmentioning
confidence: 99%